2008
DOI: 10.1027/1016-9040.13.2.114
|View full text |Cite
|
Sign up to set email alerts
|

Fluency and Cognitive Effort During First- and Second-Language Notetaking and Writing by Undergraduate Students

Abstract: This study concerns the cognitive effort expended and the difficulties experienced by undergraduate students as they took notes and wrote a text based on a lecture given in French, their primary language (L1), and in English (L2). The 21 participants had studied English (L2) for 7 years before attending the university and they had taken 3 years of intensive courses at the university in order to obtain their first diploma in English (“license”). Participants were first trained on a secondary task that allowed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
(36 reference statements)
1
12
0
Order By: Relevance
“…The obtained results indicated that participants exerted more cognitive effort when taking notes in English than in their native language of French, and overall, these individuals wrote slower when taking notes in English (Piolat et al, 2008). Similarly, when surveying international (n= 110) and American (n= 54) postsecondary-education students about their perspectives on notetaking, Dunkel and Davey (1989) found significant differences between the two groups.…”
Section: Lecture Note-takingmentioning
confidence: 81%
See 1 more Smart Citation
“…The obtained results indicated that participants exerted more cognitive effort when taking notes in English than in their native language of French, and overall, these individuals wrote slower when taking notes in English (Piolat et al, 2008). Similarly, when surveying international (n= 110) and American (n= 54) postsecondary-education students about their perspectives on notetaking, Dunkel and Davey (1989) found significant differences between the two groups.…”
Section: Lecture Note-takingmentioning
confidence: 81%
“…However, indirect evidence suggests that strong language skills facilitate note-taking proficiency. For instance, Piolat et al (2008) examined the notetaking skills of undergraduates who were non-native (yet proficient) English speakers (N=21).…”
Section: Lecture Note-takingmentioning
confidence: 99%
“…However, this skill is accorded more and more importance owing to the use of computers in class, particularly when teachers are confronted with excessive use of the copy and paste functions and the difficulties encountered by their pupils in integrating selected information. The utility of teaching this skill is strengthened by research data which point out the importance of notetaking in knowledge learning (Piolat, Barbier, & Roussey, 2008;Titsworth & Kiewra, 2004). The present study investigates how website users process written language through notetaking in L2.…”
Section: Introductionmentioning
confidence: 94%
“…Several other studies have been quasi-experimental investigations which aimed at testing the role of LCS teaching on listening achievement in general as well as on various other relevant factors (Goh, 2006;Shang, 2008;Coşkun, 2010;Bidabadi, & Yamat, 2011;Bozorgian & Pillay, 2013;Rasouli, Mollakhan, & Karbalaei, 2013 etc.). Piolat (2008) has informed that listening is usually considered a difficult skill as compared to other language skills as listeners have to simultaneously manage factors like speed of delivery, paucity of chances of the text repetition, limited vocabulary of listeners and lapses in concentration during extended listening texts. Research has also reported during the process of listening, learners need to comprehend and perceive the spoken texts "in order to make sense of it.…”
Section: Literature Reviewmentioning
confidence: 99%